Differential proliferation rates generate patterns of mechanical tension that orient tissue growth. (10th September 2013) - Mao, Yanlan; Tournier, Alexander L; Hoppe, Andreas; Kester, Lennart; Thompson, Barry J; Tapon, Nicolas
<x xml:space="preserve">Abstract</x> Orientation of cell divisions is a key mechanism of tissue morphogenesis. In the growing Drosophila wing imaginal disc epithelium, most of the cell divisions in the central wing pouch are oriented along the proximal–distal (P–D) axis by the Dachsous‐Fat‐Dachs planar polarity pathway. However, cells at the periphery of the wing pouch instead tend to orient their divisions perpendicular to the P–D axis despite strong Dachs polarization. Here, we show that these circumferential divisions are oriented by circumferential mechanical forces that influence cell shapes and thus orient the mitotic spindle. We propose that this circumferential pattern of force is not generated locally by polarized constriction of individual epithelial cells. Instead, these forces emerge as a global tension pattern that appears to originate from differential rates of cell proliferation within the wing pouch. Accordingly, we show that localized overgrowth is sufficient to induce neighbouring cell stretching and reorientation of cell division. Our results suggest that patterned rates of cell proliferation can influence tissue mechanics and thus determine the orientation of cell divisions and tissue shape.